Economic evaluation of covered stents for transjugular intrahepatic portosystemic stent shunt in patients with variceal bleeding and refractory ascites secondary to cirrhosis - Dhiraj Tripathi; David Patch; Guruprasad Aithal; Richard Mattock; Frank O'Neill; Joyce Craig; Jennifer Tanner (BMJ Open Gastroenterology)
Objectives Transjugular intrahepatic portosystemic stent shunt (TIPSS) is clinically effective in variceal bleeding and refractory ascites; however, the cost-effectiveness of TIPSS has yet to be evaluated in the UK. This study aimed to establish the cost-effectiveness of (i) pre-emptive TIPSS versus endoscopic band ligation (EBL) in populations with variceal bleeding and (ii) TIPSS versus large volume paracentesis (LVP) in refractory ascites.Methods A cost-utility analysis was conducted with the perspective including healthcare costs and quality-adjusted life years (QALYs). A Markov model was constructed with a 2-year time horizon, health states for mortality and survival and probabilities for the development of variceal bleeding, ascites and hepatic encephalopathy. A survival analysis was conducted to extrapolate 12-month to 24-month mortality for the refractory ascites indication. Uncertainty was analysed in deterministic and probabilistic sensitivity analyses.Results TIPSS was cost-effective (dominant) and cost saving for both indications. For variceal bleeding, pre-emptive TIPSS resulted in 0.209 additional QALYs, and saved £600 per patient compared with EBL. TIPSS had a very high probability of being cost-effective (95%) but was not cost saving in scenario analyses driven by rates of variceal rebleeding. For refractory ascites, TIPSS resulted in 0.526 additional QALYs and saved £17 983 per patient and had a 100% probability of being cost-effective and cost saving when compared with LVP.Conclusions TIPSS is a cost-effective intervention for variceal bleeding and refractory ascites. TIPSS is highly cost-saving for refractory ascites. Robust randomised trial data are required to confirm whether pre-emptive TIPSS is cost saving for variceal bleeding.